2010
DOI: 10.1016/j.ahj.2010.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Novel risk factors in long-term hypertension incidence in type 1 diabetes mellitus

Abstract: Background-Data from longitudinal studies suggest that biomarkers of inflammation and endothelial dysfunction are associated with development of hypertension. None of these studies have examined the association of these markers with hypertension risk in persons with diabetes. We examined the associations of inflammatory and endothelial dysfunction markers with long-term hypertension incidence in persons with type 1 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 57 publications
5
23
0
Order By: Relevance
“…Hyperhomocysteinemia is typically defined as levels >10μmol/L in reported studies [25], [26] and [27]. Levels of tHcy measured in our DCCT/EDIC cohort are comparable to observed tHcy concentrations in other studies of T1DM of similar time frame and/or participant characteristics [3], [6], [28] and [29]. While we lacked a non-diabetic control group, the observed tHcy levels in our cohort are also similar or lower than in other studies of apparently healthy non-diabetic subjects [30], and may reflect healthy dietary habits among our study participants, and for some (46%), the use of multivitamins (likely to contain tHcy-lowering B-group vitamins).…”
Section: Discussionsupporting
confidence: 77%
“…Hyperhomocysteinemia is typically defined as levels >10μmol/L in reported studies [25], [26] and [27]. Levels of tHcy measured in our DCCT/EDIC cohort are comparable to observed tHcy concentrations in other studies of T1DM of similar time frame and/or participant characteristics [3], [6], [28] and [29]. While we lacked a non-diabetic control group, the observed tHcy levels in our cohort are also similar or lower than in other studies of apparently healthy non-diabetic subjects [30], and may reflect healthy dietary habits among our study participants, and for some (46%), the use of multivitamins (likely to contain tHcy-lowering B-group vitamins).…”
Section: Discussionsupporting
confidence: 77%
“…Our findings also suggest that sVCAM-1 seems to causally underlie the development of hypertension. This observation is in striking agreement with the only prospective study thus far that has examined CAMs and pro-inflammatory cytokines as predictors of incident hypertension among individuals with type 1 diabetes [43]. Indeed, in that study only the baseline levels of sVCAM-1 (but not sICAM-1, CRP, IL-6 and TNF-α) were associated with the 15 year cumulative incidence of hypertension.…”
Section: Discussionsupporting
confidence: 78%
“…However, this was not a sample with T1D. In a longitudinal study of adults with T1D, researchers found that after controlling for BMI, endothelial dysfunction was strongly associated with the development of hypertension (Sahakyan, Klein, Myers, Tsai, & Klein, 2010). Unfortunately, our data do not allow for a causal explanation of the association between these two risk factors for CVD.…”
Section: Discussionmentioning
confidence: 99%